A randomized, controlled trial of efficacy and safety of Anbainuo, a bio-similar etanercept, for moderate to severe rheumatoid arthritis inadequately responding to methotrexate. Issue 9 (September 2016) - Chen, Xiao-Xiang; Li, Zhan-guo; Wu, Hua-xiang; Zhao, Dong-bao; Li, Xing-fu; Xu, Jian-hua; Tao, Yi; Yang, Nan-ping; Hu, Shao-xian; Huang, An-bin; Jiang, Lin-di; Wang, Guo-chun; et al.
Abstract The objective of the study was to evaluate the efficacy and safety of etanercept (Anbainuo) treatment in Chinese moderate to severe rheumatoid arthritis (RA) with inadequate response to methotrexate (MTX-IR); 600 patients (360 in phase III-1 and 240 in phase III-2) poorly responding to MTX were enrolled in the study and randomized at a ratio of 2:1 into an Anbainuo treatment or control group. The study was designed as a 12-week double-blind, placebo-controlled period followed by a 12-week open-label study. The primary endpoint was the ACR20 response rate at week 12. Secondary endpoints included the ACR50, ACR70, ACR-N, and safety. At week 12, ACR20 response was observed in 60.9 % of the Anbainuo group—significantly higher than that of the control group (20.6 %). At week 24, the ACR20 response in the Anbainuo group increased to 70.2 %; there was no significant difference compared with that of the control group (61.8 %, P  > 0.05). At week 12, the ACR50 and ACR70 responses of the Anbainuo group increased to 25.6 and 6.8 %, compared to 4 and 1 % in the control group (P  < 0.001, P  = 0.002). The ACR-N was 2.85 ± 6.73 vs. −3.24 ± 8.78 % in the control group (P  < 0.001). During the first 12 weeks of treatment, 66 adverse events (AE) were reported in the Anbainuo group (15.6 %) and 21 AEs (10.5 %) occurred in the control group, whereby the rate of the Anbainuo group was slightly higher than the control group (P  = 0.042). Severe adverse events (SAEs) occurred in the Anbainuo group (1.3 %) and one (SAE) occurred in the control group (0.5 %) (P  = 0.19). Anbainuo displays a rapid onset of efficacy as well as good tolerance and safety in MTX-IR patients having moderate to severe RA.